Effectiveness of giving oxytocin massage and klabet seed tea (Trigonella Foenum-Graceum L) on increasing breast milk production - Cantika Putri Susanto, Valencia; Nuraini, Indria; Hubaedah, Annah (Jurnal Kebidanan Indonesia, 2025)
Background: Breast milk is the main source of nutrition for babies which is easily digested by their digestive system. However, there are various reasons why mothers stop breastfeeding, one of which is because of insufficient breast milk production. One effort to increase breast milk production naturally is through non-pharmacological therapy, such as oxytocin massage which plays a role in improving blood circulation, stretching muscles, and increasing the production of the hormone oxytocin. In addition, klabet seed tea is known to have estrogenic effects thanks to its saponin, alkaloid, and flavonoid content. Purpose: The purpose of this study was to determine the effectiveness of providing oxytocin massage and klabet seed tea (Trigonella Foenum-Graceum L.) on increasing breast milk production. Methode: This study was conducted at TPMB Tutut Ismayanti and TPMB Suprihtin. Research design Pre-Experimental One group Pretest Postest Design. The population of postpartum mothers who experienced insufficient breast milk production was 42 respondents, with a purposive sampling technique and a sample size of 38 respondents with insufficient breast milk production. Oxytocin massage and klabet seed tea 3g a day were given twice a day for 7 days. The research instrument used observation sheets and SOPs. Data analysis was carried out Univariately in the form of frequency distribution and Bivariately using the Paired Sample T-test. Results: The results of the study were that postpartum mothers' breast milk production before intervention was mostly substandard (52.63%) with a mean value of 3.37 and breast milk production after intervention increased to smooth (63.16%) with a mean value of 5.76. Results of Paired Sample T-test ρ-value 0.000 <0.05. Conclusion: There is Effectiveness of Giving Oxytocin Massage and Klabet Seed Tea (Trigonella Foenum Graceum L.) to Increase Breast Milk Production. Oxytocin massage and klabet seed tea are very useful in helping to facilitate breast milk production economically on days 1-10 after giving birth.